1996
DOI: 10.1097/00007890-199610270-00026
|View full text |Cite
|
Sign up to set email alerts
|

Monosegmental Liver Transplantation From an Adult to an Infant

Abstract: A shortage of small pediatric organ donors has led to the development of reduced size liver transplantation in children. However, the discrepancy between donor and recipient weight can limit the use of this procedure despite transplantation of the left lobe only. Monosegmental liver transplantation using segment III only was recently described. We report here the case of an 11 month old, 6.9 kg boy who received another monosegmental graft (segment II) from a 78 kg donor on an urgent basis. Because of the lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…As only 40% of infants undergoing LT are able to have their abdomen closed primarily, DPC has become common practice even in this era of reduced-sized liver grafts [4]. Some studies have indicated that DPC increases the risk of wound complications including wound infection, dehiscence, and incisional hernias [4,21]. Our study refutes these findings.…”
Section: Discussionsupporting
confidence: 82%
“…As only 40% of infants undergoing LT are able to have their abdomen closed primarily, DPC has become common practice even in this era of reduced-sized liver grafts [4]. Some studies have indicated that DPC increases the risk of wound complications including wound infection, dehiscence, and incisional hernias [4,21]. Our study refutes these findings.…”
Section: Discussionsupporting
confidence: 82%
“…Nine publications were identified from 1995 to 2004 5–13. A total number of patients from 7 publications were analyzed, because 2 publications from the same institution appeared to represent partial data from other publications by the same team 10, 11.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome a weight discrepancy of more than 10:1 from donor to recipient, a further reduction of the left lateral segment to a monosegment may be necessary, as has been done with cadaveric5–8 and living related donors (LRD) 9–13. The subsequent reduction could be performed in situ, at the donor operation7, 9, 12 or at the back table procedure,5, 6, 8 with the utilization of the segment II6, 8, 9 or III5, 7, 12, 13 as grafts. The small sample size of reported data from each study on monosegmental liver transplantation (MLT), different donor status (cadaveric or living), and technical reduction of segment II or III make it difficult to draw conclusions about indication and outcome of monosegmental grafts.…”
mentioning
confidence: 99%
“…The first report of an S2 graft was described by Mentha et al, who used a methylene blue injection to confirm the demarcation line between segments 2 and 3 [11]. When preparing an S2 graft, the left superficial hepatic vein and tributary vein are important when harvesting the graft liver.…”
Section: Discussionmentioning
confidence: 99%